The Gambia : First Review Under the Extended Credit Facility Arrangement, Financing Assurances Review, and Request for Augmentation of Access and a Waiver of Nonobservance of a Performance Criterion-Press Release; Staff Report; and Statement by the Executive Director for The Gambia. (IMF Staff Country Reports; Country Report ;, 2021)
The IMF Executive Board approved, on March 23, 2020, a 39-month Extended Credit Facility (ECF) arrangement in the amount of SDR 35 million (56.3 percent of quota) for The Gambia. The Gambia benefited from a Rapid Credit Facility (RCF) disbursement of SDR 15.55 million (25 percent of quota) approved on April 15, 2020 and is receiving debt service relief under the Catastrophe Containment and Relief Trust (CCRT) expected to total SDR 7.9 million (SDR 4.2 million of which has already been approved), to help meet heightened balance-of-payments and fiscal financing needs due to the impact of the COVID-19 pandemic. While indicators point to a domestic weakening of the pandemic, the authorities are seeking an ECF augmentation of SDR 20 million (32.15 percent of quota) to meet balance-of-payments needs arising from fiscal measures to stimulate the economic recovery in 2021, strengthen public health preparedness, increase social spending to mitigate the effects of the pandemic. They are also requesting a waiver of nonobservance of a continuous performance criterion (a zero ceiling) on new external payment arrears of the central government.